Enhancement of runaway production by resonant magnetic perturbation on J-TEXT. (15th June 2016) - Chen, Z.Y.; Huang, D.W.; Izzo, V.A.; Tong, R.H.; Jiang, Z.H.; Hu, Q.M.; Wei, Y.N.; Yan, W.; Rao, B.; Wang, S.Y.; Ma, T.K.; Li, S.C.; et al.
Abstract: The suppression of runaways following disruptions is key for the safe operation of ITER. The massive gas injection (MGI) has been developed to mitigate heat loads, electromagnetic forces and runaway electrons (REs) during disruptions. However, MGI may not completely prevent the generation of REs during disruptions on ITER. Resonant magnetic perturbation (RMP) has been applied to suppress runaway generation during disruptions on several machines. It was found that strong RMP results in the enhancement of runaway production instead of runaway suppression on J-TEXT. The runaway current was about 50% pre-disruption plasma current in argon induced reference disruptions. With moderate RMP, the runway current decreased to below 30% pre-disruption plasma current. The runaway current plateaus reach 80% of the pre-disruptive current when strong RMP was applied. Strong RMP may induce large size magnetic islands that could confine more runaway seed during disruptions. This has important implications for runaway suppression on large machines.